Absolute Bioavailability of Osimertinib in Healthy Adults. Issue 2 (23rd April 2018) - Vishwanathan, Karthick; So, Karen; Thomas, Karen; Bramley, Alex; English, Stephen; Collier, Jo
Abstract: Osimertinib is a third‐generation, central nervous system–active, epidermal growth factor receptor–tyrosine kinase inhibitor (EGFR‐TKI) selective for EGFR‐TKI sensitizing and T790M resistance mutations. This phase 1, open‐label study (NCT02491944) investigated absolute bioavailability and pharmacokinetics (PK) of oral and intravenous (IV) osimertinib. Ten healthy subjects (21–61 years) received a single oral 80‐mg dose concomitantly with a 100 μg (containing 1 μCi) IV microtracer dose of [ 14 C]osimertinib. Oral and IV PK were determined simultaneously for osimertinib and its active metabolites, AZ5104 and AZ7550. High‐performance liquid chromatography and accelerator mass spectrometry were used to characterize IV dose PK. Geometric mean absolute oral bioavailability of osimertinib was 69.8% (90% confidence interval, 66.7, 72.9). Oral osimertinib was slowly absorbed (median time to maximum plasma concentration [tmax ] 7.0 hours). Following tmax, plasma concentrations fell in an apparent monophasic manner. IV clearance and volume of distribution were 16.8 L/h and 1285 L, respectively. Arithmetic mean elimination half‐life estimates were 59.7, 52.6, and 72.6 hours for osimertinib, AZ5104, and AZ7550, respectively (oral dosing), and 54.9, 68.4, and 99.7 hours for [ 14 C]osimertinib, [ 14 C]AZ5104, and [ 14 C]AZ7550, respectively (IV dosing). Oral osimertinib was well absorbed. Simultaneous IV and oral PK analysis proved useful for complete understanding of osimertinib PK and showed that the first‐pass effect was minimal for osimertinib.